DNA damage response and resistance of cancer stem cells. (1st April 2020) - Abad, Etna; Graifer, Dmitry; Lyakhovich, Alex
Abstract: The cancer stem cell (CSC) model defines tumors as hierarchically organized entities, containing a small population of tumorigenic CSC, or tumour-initiating cells, placed at the apex of this hierarchy. These cells may share common qualities with chemo- and radio-resistant cancer cells and contribute to self-renewal activities resulting in tumour formation, maintenance, growth and metastasis. Yet, it remains obscure what self-defense mechanisms are utilized by these cells against the chemotherapeutic drugs or radiotherapy. Recently, attention has been focused on the pivotal role of the DNA damage response (DDR) in tumorigenesis. In line with this note, an increased DDR that prevents CSC and chemoresistant cells from genotoxic pressure of chemotherapeutic drugs or radiation may be responsible for cancer metastasis. In this review, we focus on the current knowledge concerning the role of DDR in CSC and resistant cancer cells and describe the existing opportunities of re-sensitizing such cells to modulate therapeutic treatment effects. Highlights: A subpopulation of cancer stem cells (CSC) sharing similar qualities with chemo- and radio-resistant cancer cells is responsible for tumor initiation, maintenance and recurrence and they appear to be more resistant owing to their enhanced DNA damage response (DDR). Consequently, cancer cells are often more reliant on a subset of repair pathways and are therefore more susceptible to DDR inhibition than are normal cells that maintain full DNA-repair/DDR capacity. The targeted inhibition of DDR-related proteins can contribute to eradicate the CSC population aiming at sensitizing resistant cancer cells to treatments.